A tale of three cities: Climate heterogeneity - María Dolores Gadea; Jesús Gonzalo (SERIEs - Journal of the Spanish Economic Association, 2022)
Professor Dolado has developed much of his professional career in three cities: Zaragoza, Oxford and Madrid. This fact, together with the recent appearance of literature relating climate with human behavior, has inspired us to analyze a set of relevant climate change issues linked to these areas, particularly any possible heterogeneity. The novel methodology proposed in (Gadea Rivas and Gonzalo in J Econom 214:153-174, 2020a for analyzing a wide range of characteristics of the temperature distribution (converting them into time series objects), instead of focusing solely on the mean, allows us to carry out this analysis . Using this methodology, we can identify local warming patterns within the global warming phenomenon of different types and intensities. The results show that there is a clear warming process in the three areas. The two Spanish cities (Zaragoza and Madrid) have many similarities, but Oxford fits into a different type of warming category. The former are characterized by higher trends in the upper quantiles than in the lower, an increase in dispersion, acceleration and an "upper amplification" with respect to the mean. In Oxford, the type of climate change is different, displaying higher trends in the lower quantiles, a weak negative trend in dispersion, "lower amplification" and a more attenuated acceleration in recent decades. There is no doubt that a better knowledge of local warming heterogeneity is recommendable for the design of more effective mitigation policies. The influence of the climate on human behavior and, specifically, on Professor Dolado's personality, takes us into lesser-known regions which are left for the reader to discern.
Keywords: C31; C32; Q54; 330; Climate change; Distributional characteristics; Functional stochastic processes; Global Warming; Local Warming; Quantiles; Temperature distributions; Trends